The Capital Punishment for Narcotic Crime: Pros and Cons in Indonesian Legal System - Syigit Dony Kurniawan (The Indonesian Journal of International Clinical Legal Education, 2020)
The implementation of the death penalty to the perpetrators of narcotic crime lately has been widely applied, it aims to give deterrent effect. The goverment has made many laws to prevent the narcotics crime. However, narcotic crime can be immediately lost from this country, because there are still many violate this law with still a lot perpetrators of narcothics caught by the autorities shows that the law in this country is still very weak. There needs to be a good law enforcement because it is well known to many that police and soldiers are also involved in drug trafficking as a â€œbackingâ€ for drug kingpin. This is certinly is very embrrassing thing because the police who are supposed to eradicate crimes are secretly involved in the crime itself, this is certainly verry worrying because if the police are involved in this crime let alone ordinary people. Certainly a lot of things we need to improve, the first is a legislation that should be more stringent and more strich punishment such as the death penalty itself, because with strich rules and firmly then then the perpetrators will think repeatedly to commit the crime. Secondly, need for self awareness in law enforcement like the police, they must realize that they are the key to eradication of drug trafficking in this country, they must be able to work well and professionally to keep their good name and combating this narcothics crime.